2021
DOI: 10.18632/aging.203593
|View full text |Cite
|
Sign up to set email alerts
|

DCP1A is an unfavorable prognostic-related enhancer RNA in hepatocellular carcinoma

Abstract: Long non-coding RNAs (lncRNAs) are associated with occurrence and development of tumors. Enhancer RNA (eRNA) is a special type of lncRNAs produced from transcription of enhancer elements. The function of eRNAs in tumors have elicited significant attention recently. However, the clinical significance and role of eRNAs in hepatocellular carcinoma (HCC) has not been fully explored. The current study sought to explore the expression level and prognostic value of key eRNAs in HCC. Bioinformatics analyses were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Results for the GO, KEGG and REACTOM pathways likewise showed that DCP1a is involved in other cancer-related pathways, such as the Notch signalling pathway, embryonic skeletal system development, vasculature development, and the mitotic cell cycle pathway (Figure 4D; Supplementary Figure S5E–H). These results are consistent with recent findings that DCP1a is strongly associated with embryonic growth and tumour development (Ibayashi et al , 2021; Wu et al , 2018; Wu et al , 2021a), and suggest that DCP1a is more strongly associated with cancer than is DCP1b. Furthermore, we noted that the activation of capped intron-containing pre-mRNA processing was evident in both DCP1a-and DCP1b-deficient cells (Supplementary Figure S5H).…”
Section: Resultssupporting
confidence: 93%
“…Results for the GO, KEGG and REACTOM pathways likewise showed that DCP1a is involved in other cancer-related pathways, such as the Notch signalling pathway, embryonic skeletal system development, vasculature development, and the mitotic cell cycle pathway (Figure 4D; Supplementary Figure S5E–H). These results are consistent with recent findings that DCP1a is strongly associated with embryonic growth and tumour development (Ibayashi et al , 2021; Wu et al , 2018; Wu et al , 2021a), and suggest that DCP1a is more strongly associated with cancer than is DCP1b. Furthermore, we noted that the activation of capped intron-containing pre-mRNA processing was evident in both DCP1a-and DCP1b-deficient cells (Supplementary Figure S5H).…”
Section: Resultssupporting
confidence: 93%
“…The two genes that define the significant GO terms are Decapping MRNA 1A (DCP1A) and C-Reactive Protein (CRP). We found two intronic variants with allele frequency <0.45 and 2 upstream variants within the TFBS of DCP1A, which is a biomarker used for gastric [ 85 ], colorectal [ 86 ], and hepatocellular cancer progression [ 87 ]. Six variants were found downstream of the CRP gene, which is an inflammatory biomarker closely associated with prognosis in lung and gastric cancers, as well as those involving PD1 [ 88 , 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“… 236 , 237 In HCC, eRNA-APH1A is highly expressed in advanced tumor stages with larger tumor sizes and higher histological grades. 238 Furthermore, many immune-related eRNAs (IReRNAs) were identified in HCC, and the prognostic role of IReRNAs was explored. Five IReRNAs (AC073257.2, AL445524.1, FAM120AOS, LINC00513, and STK3) were identified as an IReRNA signature (IReRS), and they are positively correlated with poor survival but inversely correlated with CD8 + T cells and M0 macrophage infiltration in HCC, especially AL445524.1.…”
Section: Conclusion and Discussionmentioning
confidence: 99%